Does Factoring Solving The Financing Problems And Difficulties Faced By Smes In Arab Countries? International Experiences - Melikaoui, Mouloud (جامعة الوادي - University of Eloued, 2019)
The present paper aims at discusses the factoring as a modern financing alternative for SMEs given the funding difficulties faced by this type of institutions in Arab countries, either banking and financial enterprises or financial markets, on the grounds that these institutions have special characteristics distinguish them from large institutions including the high risk and uncertainties that characterize their future. This financing mechanism is also in line with the advantages of SMEs in terms of the low cost of financing and the degree of risk related to the financial hardship of the debtor which is the responsibility of the factor enterprise. The study found that there is a growing global trend towards using factoring as a modern financing mechanism for SMEs at the expense of traditional financing methods by presenting both the Romanian and the Mexican experience
مقال
Keywords: financing problems ; factoring ; SMEs ; Arab countries ; international experiences